Media and the Politics of Failure - Roselle, L. author. aut Link
VII, 191 p.
Keywords: Roselle analyzes how political leaders of powerful states use media to explain military defeats. The cases of the United States in Vietnam and the Soviet Union in Afghanistan highlight the role of great power identity, domestic politics, and media structure.